Spread of Multidrug-Resistant Microorganisms - Silvia Di Lodovico; Teresa Fasciana; Mara Di Giulio; Luigina Cellini; Anna Giammanco; Gian Maria Rossolini; Alberto Antonelli (MDPI AG, 2022)
Multidrug-resistant organisms (MDRO) are bacteria that exhibit acquired resistance to multiple antibiotics, reducing the efficacy of antimicrobial therapies [...]